PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PERHUBUNGAN KABUPATEN TANA TORAJA - Meytiransi Remen; Adriana Madya Marampa; Rahma G Tammu (Universitas Nusa Cendana, 2023)
The purpose of this study was to find out whether there is an influence of work motivation and discipline on employee performance at the Tana Toraja District Transportation Office. The population size is 37 people, all of whom are respondents in this study. This study uses primary data obtained by distributing questionnaires to employees at the Tana Toraja District Transportation Office. The analysis technique used is multiple linear regression, which is operated through the SPSS 25. The results showed that motivation had an effect on employee performance, and work discipline affected employee performance. Motivation and work discipline simultaneously have a positive and significant effect on employee performance at the Tana Toraja District Transportation Office. The results of this study can be concluded that the higher the motivation and work discipline on employee performance, the higher employee performance will be. Keywords: Work Discipline; Motivation; Employee Performance